A Lens between Nature and Death. Cemeteries: The Staging of New Hybrid Landscapes, Places where Symbiosis Generates Life (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2025)
Lichens are an association of species: a plant organism originating from the symbiosis between a fungus and an alga, capable of transforming an apparently lifeless place into a space suitable for life. The organism resulting from this symbiosis is a new individual, suspended between the kingdoms of Fungi and Plantae. ‘Marginality’ is not only a condition inherent in their biological structure but also determines the environment in which they perform their vital functions: in a state that would be extreme for most complex organisms, lichens make the ‘liminal’ zone their habitat. Classified by ecological sciences as ‘pioneer species’, they inhabit spaces, leading them into a constant transition state. Thanks to them, the residual spaces of death have the potential to transform into spaces ready to host life; through their bodies – the thalli – they convert the voids scattered within the minute ecological network characterising the cemetery space. The analysis proposed in the text explores the condition of lichens – both from a scientific and metaphorical, and consequently theoretical, perspective – and their impact on a place that is also symbolic of marginality: The Monumental Cemetery of Verano. The result is a series of changing images, developed through an abstraction of the traditional scientific method, yielding concentric universes: evocative images, following the path traced mid-last century by György Kepes with The New Landscape in Art and Science. This aims to represent the tension developing in the abandoned spaces of cities and the possibilities arising from it.
Keywords: landscape; nature; Rome